2016
DOI: 10.1371/journal.pone.0159295
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals Disruption of Innate Immunity in Chronic Heavy Ethanol Consuming Female Rhesus Macaques

Abstract: It is well established that heavy ethanol consumption interferes with the immune system and inflammatory processes, resulting in increased risk for infectious and chronic diseases. However, these processes have yet to be systematically studied in a dose and sex-dependent manner. In this study, we investigated the impact of chronic heavy ethanol consumption on gene expression using RNA-seq in peripheral blood mononuclear cells isolated from female rhesus macaques with daily consumption of 4% ethanol available 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 130 publications
4
40
0
Order By: Relevance
“…Differential expression of the JAK/STAT pathway was observed in the nucleus accumbens (Mamdani et al, 2015). Alterations in JAK/STAT signaling were also found in rhesus macaques chronically exposed to ethanol (Asquith et al, 2014; Sureshchandra et al, 2016). Thus, in addition to changes in canonical TLR signaling, chronic ethanol exposure alters many other immune signaling pathways (i.e.…”
Section: Functional Systems Associated With Alcohol Dependencementioning
confidence: 96%
“…Differential expression of the JAK/STAT pathway was observed in the nucleus accumbens (Mamdani et al, 2015). Alterations in JAK/STAT signaling were also found in rhesus macaques chronically exposed to ethanol (Asquith et al, 2014; Sureshchandra et al, 2016). Thus, in addition to changes in canonical TLR signaling, chronic ethanol exposure alters many other immune signaling pathways (i.e.…”
Section: Functional Systems Associated With Alcohol Dependencementioning
confidence: 96%
“…Specifically, using this model, we have shown that CMD enhances while CHD attenuates vaccine responses 42,44,47 . More recently, we reported significant transcriptional changes in PBMC from female rhesus macaque following 12 months of CHD using RNA-Seq and concluded that the circulating innate immune cells bear the largest burden of chronic heavy drinking 46 . Therefore, in this study, we investigated the impact of both CHD and CMD on PBMC transcriptional profile and immune mediator production at resting and after stimulation with lipopolysaccharide (LPS) using samples obtained from three cohorts of male rhesus macaques that followed a standard protocol of daily open-access to 4% ethanol in water solution for over 12 months.…”
Section: Introductionmentioning
confidence: 97%
“…This model presents a unique opportunity to study the impact of chronic voluntary moderate/heavy drinking on immunity in a highly translational outbred animal model without any overt tissue damage. We have leveraged this model to define the impact of chronic drinking on circulating and tissue resident immune cells 4146 . Specifically, using this model, we have shown that CMD enhances while CHD attenuates vaccine responses 42,44,47 .…”
Section: Introductionmentioning
confidence: 99%
“…in 1999 demonstrated that alcohol impairs T‐cell function and neutrophil chemotaxis, which can alter immune responses, increasing the risk of periodontitis . Ethanol modulates the function of monocytes in a dose‐ and time‐dependent manner . Monocytes also express Toll‐like receptor (TLR) 4, which is the receptor responsible for recognizing endotoxin lipopolysaccharides (LPS) on the surface of Gram‐negative bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…9 Ethanol modulates the function of monocytes in a dose-and time-dependent manner. 10 Monocytes also express Toll-like receptor (TLR) 4, which is the receptor responsible for recognizing endotoxin lipopolysaccharides (LPS) on the surface of Gram-negative bacteria. 11 Upon LPS binding, monocytes become activated and mature into macrophages, which in turn migrate into tissues where they respond to infection by secreting several cytokines, resulting in the recruitment of additional leukocytes via production of chemokines and antigen presentation to T cells.…”
Section: Introductionmentioning
confidence: 99%